Cardiorespiratory coordination reveals training-specific physiological adaptations - Garcia-Retortillo, S; Gacto, M; O'Leary, T J; Noon, M; Hristovski, R; Balagué, N; Morris, M G (Springer Science and Business Media LLC, 2019)
To compare the effects of high-intensity interval training (HIIT) and moderate-intensity training (CONT), matched for total work, on cardiorespiratory coordination and aerobic fitness.